Triple X Syndrome with a Rare Finding: Cleft Palate - Esra Gürkaş; Hülya Maraş Genç; Esra Kılıç (Galenos Yayinevi, 2018)
Triple X syndrome (trisomy X) is a sex chromosomal anomaly caused by the presence of an extra X chromosome. The patients with Triple X syndrome have a wide range of phenotypic variability. Some individuals are only mildly affected or asymptomatic. Epicanthal folds, clinodactyly, tall stature and hypotonia are the most commom phenotypic features. Patients also may have seizures, genitourinary abnormalities and premature ovarian failure. We report a patient with Triple X syndrome and cleft palate. By describing this case, we want to draw attention to the association between cleft palate and Triple X syndrome.